Impact of water resources management on area under cultivation level and agricultural production efficiency (Case Study: Villages of Zebarkhan district of Neyshabur city) - Kariznovi, Ali; Jafari, Hamid (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
The amount of water consumed in the agricultural sector in Iran is higher than the global average and this necessitates more attention to proper water management in this sector. Due to the climatic conditions of Iran, the average rainfall in most areas is lower than global rainfall. That is to say, the water issue is one of Iran's most important concerns or the greatest challenge for the people of this land. Examining the current agricultural situation indicates that despite the increased agricultural production potential due to the lack of a proper management system, optimal utilization of available resources has not become possible and droughts and reduced rainfall and increasing population followed reduce the amount of water consumed in the agricultural sector. The present study investigates the impact of agricultural water resources management on the economic development of rural settlements (Case study: Villages of Zebarkhan district of Neyshabur city). This research is applied in terms of purpose and in terms of descriptive and analytical method and library and field methods have been used for data collection. According to the results of the present study and data analysis regarding the amount of water consumed in the study area, it was observed that the amount of water consumed per hectare for all crops in modern management lands was less than the fields where managed by the traditional way. This suggests that modern science-based scientific management has played a key role in reducing the loss of water resources within the scope of this study, and in contrast, water loss in farms that are managed in traditional ways is so high. Also, regarding the production efficiency in the study area, the results showed that the production efficiency per hectare for all crops was significantly higher than that under traditional management. This rate varied between 25 to 57.1%.